Diversity of bacterial endosymbionts of Bemisia tabaci from some regions in Indonesia and the genetic diversity of Wolbachia endosymbiont - NADIYAH HIDAYATI; ALAN SOFFAN; TRIWIDODO ARWIYANTO; ARMAN WIJONARKO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Hidayati N, Soffan A, Arwiyanto T, Wijonarko A. 2024. Diversity of bacterial endosymbionts of Bemisia tabaci from some regions in Indonesia and the genetic diversity of Wolbachia endosymbiont. Biodiversitas 25: 4304-4314. Bemisia tabaci Gennadius 1889 (Hemiptera) is an insect that associates with endosymbiont bacteria to meet nutritional needs lacking in its food. The species has both primary and secondary endosymbionts, with infections showing significant dynamism among populations. Wolbachia is a facultative endosymbiont that infects 66% of all insect species, including B. tabaci, which is a key focus of this study. The study aimed to investigate the diversity of bacterial endosymbiont infections in several B. tabaci populations collected from Java and Sumatra, Indonesia, to explore the genetic diversity of Wolbachia endosymbiont. The B. tabaci population was collected from 17 districts in Java and Sumatra, and to determine the presence of bacterial endosymbiont was determined through molecular analysis using specific primers. The study involved a comprehensive methodology, including the construction and comparison of multiple alignment sequences, phylogenetic analysis, and genetic differentiation of Wolbachia in 10 representative populations of B. tabaci, which were then compared with Wolbachia sequences from other countries and arthropods. The results showed the presence of various bacterial endosymbionts found among the B. tabaci populations, including Candidatus portiera, Arsenophonus sp., Cardinium sp., Hamiltonella sp., Wolbachia sp., and Rickettsia sp. Wolbachia was found in all B. tabaci samples, while other endosymbiont bacteria varied quite widely among all B. tabaci population samples. The genetic diversity of Wolbachia of B. tabaci from Indonesia showed close relatedness and has a different clade from Wolbachia from other countries and arthropods. The population structure of Wolbachia populations from Java was genetically related and similar to that of Wolbachia from Sumatra.